Characterizing and predicting the relationship between translaminar fracture toughness and pull-out length distributions under distinct temperatures. (9th January 2023) - Yu, B.; Katafiasz, T. J.; Nguyen, S.; Allegri, G.; Finlayson, J.; Greenhalgh, E. S.; Pinho, S. T.; Pimenta, S.
Abstract : The translaminar fracture toughness reflects the damage tolerance of a fibre-reinforced composite under longitudinal tension, which often governs the final failure of structures. One of the main energy-dissipation mechanisms that contributes to the translaminar toughness of composites is the fibre pull-out process. The present study aims to quantify and model the statistical distribution of fibre pull-out lengths formed on the translaminar fracture surface of composites, for the first time in the literature; this is done under different temperatures, so that the relationship between pull-out length distributions, micromechanical properties and the translaminar fracture toughness can be established. The fracture surfaces of cross-ply compact tension specimens tested under three different temperatures have been scanned through X-ray computed tomography to quantify the extent of fibre pull-out on the fracture surfaces; the distribution of pull-out lengths showed alarger average and larger variability with an increase in temperature, which also lead to an increase in translaminar fracture toughness. A similar trend has been captured by the proposed analytical model, which predicts the pull-out length distribution based on the analysis of quasi-fractal idealizations of the fracture surface, yielding an overall accuracy of more than 85%. This article is part of the theme issue 'Ageing and durability of composite materials'.